Entertaining to Buy: Exploring the Role of Immersion in Live Streaming and Its Influence on Purchase Intention in Student Social Commerce - Adam Fadillah; abdhy; Rika Eliana (Faculty of Law, Universitas Pekalongan, 2025)
Technology development has brought about a lot of changes in the business world, especially when it comes to online transactions, which has made the internet market quite successful. The online market has changed by using social media as a platform for e-commerce. Live streaming was the first step toward the emergence of social commerce. Because consumers have a high level of purchasing interest, which is affected by entertainment elements, live streaming has become popular. Immersion is the mediating variable used in this study to examine the indirect impact of entertainment on purchase interest. The purpose of this study is to investigate how entertainment affects consumers' inclination to buy, using social commerce live streaming as a mediating factor. A quantitative approach is used in this study, using a sample of 350 participants. A Likert scale that includes metrics for immersion, entertainment, and purchase interest is used to collect data. The study's findings show that: 1) Entertainment has a positive and significant influence on purchasing interest in social commerce live streaming, 2) Entertainment has a positive and significant impact on immersion in social commerce live streaming, 3) Immersion has a positive and significant influence on purchasing interest in social commerce live streaming, 4) Entertainment has a positive and significant influence on purchasing interest through immersion as the mediating variable in social commerce live streaming. Therefore, the influence of entertainment on consumer purchasing interest can be achieved either through immersion as a mediating variable or directly, without necessitating immersion as an intermediary.